STUDENTS’ PERCEPTION ON THE USE OF WHATSAPP FOR LEARNING ENGLISH AT SMP ISLAM AS-SHOFA - Sri Wahyuni; Jismulatif Jismulatif; Mahdum Mahdum (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2022)
This study aims to determine students' perceptions of the use of WhatsApp for learning English in SMP Islam As-Shofa and the differences between male and female perceptions about use Whatsapp. This research is a quantitative descriptive study involving 2 classes totaling 50 students. The instrument used is a questionnaire to get data easily during the pandemic. Data collection was carried out by distributing online questionnaires to 9th-grade students of SMP Islam As-Shofa via group Whatsapp to the students. The data were analyzed using a Likert scale to determine students' perceptions of using Whatsapp for learning English. The results showed that learning through whatsapp was quite feasible to use with the results of a percentage of 40% having a positive perception and for the difference between male and female students with a percentage of 24.4% of male students answering agree for positive perception, and with a percentage of 21% female students answering agree for positive perception, while for the negative perception, the result with a percentage 45.2% students answered disagree and with a percentage 22.4% female students answered disagree.